Influence of modification process parameters on the properties of crumb rubber/EVA modified asphalt. Issue 27 (5th April 2016) - Fang, Changqing; Qiao, Xiaoting; Yu, Ruien; Yu, Xin; Liu, Jianjun; Yu, Jiang; Xia, Ronghou
ABSTRACT: Crumb rubber (CR) and ethylene vinyl acetate copolymer (EVA) were adopted as asphalt modifiers. Routine tests, softening point, penetration, and ductility were used to evaluate the basic properties of crumb rubber and ethylene vinyl acetate copolymers (CR/EVA) modified asphalt. The segregation experiment measured the storage stability. Modern test methods such as fluorescence microscopic photography technology was used to study stability of polymer modified asphalt. Infrared spectrum experiment was used to analyze the composition differences of the upper part and lower part of CR/EVA modified asphalt. Matlab software was employed to fit out the formulae of ductility, penetration, and softening point difference of modified asphalt and shearing temperature, shearing time and shearing rate separately. Compared with base asphalt, the properties of CR/EVA modified asphalt have been greatly improved. The formulae which were fitted out by Matlab software showed that the shearing time was the foremost factor affecting the properties of CR/EVA modified asphalt, followed by shearing temperature, and the last was shearing rate. The conclusions which were fitted by orthogonal experiment were basically consistent with the results of formulae which were fitted out by Matlab software. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43598. Abstract :